Effect of Pilates Training with Vitamin E Supplementation on Some Metabolic Syndrome Markers in Overweight Female Adolescents - Fahimeh Karimi; Mehdi Moradi; Behrouz Baghaiee (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2018)
Introduction: Metabolic syndrome is considered as a risk factor for cardiovascular diseases and diabetes and its prevalence increases at an alarming rate. Therefore, the study aimed to evaluate the effect of six weeks of Pilates training along with Vitamin E supplementation on some markers of metabolic syndrome in female overweight adolescents. Methods: This clinical trial was conducted on 30 female adolescents aged 15-18 years in Mahallat, Iran. The subjects were randomly divided into three groups of six weeks Pilates, six weeks of Pilates + vitamin E and control. Exercises with minimum duration of 30 minutes were performed three days a week. Physiological and anthropometric indices, as well as lipid profiles and glucose level of the participants were measured in the pre-test and post-test stages through blood sampling. Data analysis was performed in SPSS version 22 using paired t-test, ANCOVA, and Bonferroni post hoc test. In addition, P-value below 0.05 was considered significant. Result: In this research, while no significant changes were observed in levels of LDL, HDL and TG of the subjects in the Pilates and vitamin E group (P≥0.05), the levels of TG (P=0.022) and glucose (P=0.001) and waist-to-hip ratio (WHR) significantly decreased after the intervention. Moreover, levels of LDL (P=0.001), TG (P=0.002), cholesterol (P=0.013), glucose (P=0.001) and WHR (P=0.004) significantly decreased in the Pilates group, whereas no significant changes were observed in the level of HDL (P≥0.05). In the control group, no significant changes were observed in the levels of LDL, HDL, TG, cholesterol and WHR of the subjects (P≤0.05). Comparison of the groups revealed a significant difference between the Pilates and control groups in terms of the levels of LDL (P=0.18) and cholesterol (P=0.024). Conclusion: According to the results of the research, Pilates training can lead to the control of lipid profile, WHR, and glucose level in overweight female adolescents. Furthermore, Pilates training along with vitamin E supplementation had similar impacts and no significant difference was observed in this regard.